Biochar for wastewater treatment – a Minireview** - Westholm, Lena Johansson (Вісник НТУУ “КПІ імені Ігоря Сікорського”. Серія: Хімічна інженерія, екологія та ресурсозбереження, 2021)
Wastewater must be treated no matter if is reused or discharged into the environment. The cost of wastewater treatment may be rather high, though other solutions are sought. One of them is the application of filter materials. The filter materials have been used for removal of various pollutants in different kinds of wastewater and a wide range of filter materials (natural products, industrial waste products or man-made products) have been investigated. Among these filter materials, biochar has attracted increasing attention during the last decade. A large number of publications are devoted to production, properties and potential applications of biochar. They reveal that biochar is capable of removing pollutants of different kinds from wastewaters. A number of experiments was focused on the removal of commonly found pollutants, e.g. nutrients, heavy metals, organic matters and pharmaceuticals. It was found that the origin of the feedstock and the thermochemical treatment method are tightly connected and will have an impact on the properties of the biochar. A large number of different feedstock material like wood or wood residues, garden wastes or human and animal wastes can be transformed into biochar by torrefaction and pyrolysis. Properties of biochar will depend on transformation method. Surface area, porosity, pH, surface charge, functional groups and mineral components contribute to a vast number of mechanisms that are responsible for the metal removal, e.g. electrostatic interaction between the surface of the biochar and the specific metal, the cation exchange capacity between metals and protons and the alkaline metals on the surface of the biochar, metal complexation with functional groups and precipitation of metals that form non-soluble compounds. Biochar was successfully applied in wetlands systems to increase the removal of some targeted pollutants.